2015
DOI: 10.1016/j.jcrs.2014.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization method for detecting the incidence of color perception changes after cataract surgery

Abstract: The author has no financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…To minimize this effect, yellow intraocular lenses (IOLs) are implanted. Miyata found that the incidence of cyanopsia was higher with clear IOLs than with yellow IOLs [45]. In our study, all of the patients had cataract surgery with implantation of the yellow AcrySof IQ Monofocal IOL a few weeks prior to scheduled vitrectomy, so we assume that cataract surgery was not significant in our evaluation of colour vision outcomes.…”
Section: Discussionmentioning
confidence: 78%
“…To minimize this effect, yellow intraocular lenses (IOLs) are implanted. Miyata found that the incidence of cyanopsia was higher with clear IOLs than with yellow IOLs [45]. In our study, all of the patients had cataract surgery with implantation of the yellow AcrySof IQ Monofocal IOL a few weeks prior to scheduled vitrectomy, so we assume that cataract surgery was not significant in our evaluation of colour vision outcomes.…”
Section: Discussionmentioning
confidence: 78%
“…The study comprised one eye of patients implanted with a UV-only filtering IOL (Acrysof SA60AT; n =57), known as Group 1, and one eye (of different patients) implanted with the blue light-filtering IOL (Hoya AF-1 YA60BB; n =96), known as Group 2, and a further reference group ( n =41) comprising healthy patients without either cataract or prior cataract surgery. 65 Although cyanopsia did occur more frequently in Group 1 than in Group 2 one month postoperatively (14.5 vs 4.9% P =0.049), this difference was no longer significant 3 months following surgery (9.1 vs 5.2% P >0.05).…”
Section: The Rationale and Evidence Base Upon Which Implantation Of Bmentioning
confidence: 78%
“…A retrospective study (evidence level 3b, Table 1 ) designed to compare the prevalence of cyanopsia (seeing everything tinged with blue) in eyes implanted with either a UV-only filtering IOL or a blue light-filtering IOL, 65 where cyanopsia was graded on the basis of white gradation cards (in a system known as the neutralization method), has been reported. The study comprised one eye of patients implanted with a UV-only filtering IOL (Acrysof SA60AT; n =57), known as Group 1, and one eye (of different patients) implanted with the blue light-filtering IOL (Hoya AF-1 YA60BB; n =96), known as Group 2, and a further reference group ( n =41) comprising healthy patients without either cataract or prior cataract surgery.…”
Section: The Rationale and Evidence Base Upon Which Implantation Of Bmentioning
confidence: 99%
“…Unlike the prolonged course of age-related cataracts, phacoemulsification surgery instantly restored the transparency of ocular media but did not modulate the increased signals. This may be a key point in interpreting subjective experiences of colour appearance postoperative, which has been termed cyanopsia [22].…”
Section: Discussionmentioning
confidence: 99%
“…By testing for achromatic settings [19, 20] and minimum motion task [21], studies have confirmed differences in perceiving short-wavelength light between patients with senile cataracts and patients undergoing cataract surgery. However, due to the lack of comparisons between the lens of middle-aged volunteers and mildly aged lens, the status of colour vision after cataract surgery has not been discussed in the context of postoperative benefits; instead, researchers have simply named this condition as cyanopsia [22]. Past studies have only measured sensitivity to lights within specific spectral ranges.…”
Section: Introductionmentioning
confidence: 99%